The Role of E-Governance Techniques in Audit Quality: E-Auditing as a Model - salahsahib, ahmed; Abdullah Ibrahim , Mohammed (Journal of Economics and Administrative Sciences, 2025)
.This study aimed to examine both the theoretical and practical aspects of electronic governance techniques and their impact on audit quality.  The role of electronic governance techniques in accomplishing the tasks for which the auditor is responsible has been illustrated by using electronic audit programs. The study also aimed to identify the most significant challenges and obstacles facing audit firms in Iraq, which hinder their adoption of modern electronic techniques in their auditing work.The practical aspects addressed one of the main tools for data collection, within the framework of achieving the researcher's research objectives, as well as verifying the research hypotheses. The researchers relied on survey lists to seek the opinions of auditors and specialists in 8) of the largest auditing companies in Iraq within the framework of explaining the relationship between electronic governance techniques and audit quality.The researchers' most important conclusions were that the success of implementing electronic techniques in auditing tasks depends not only on the quality of their implementation, but also on the availability of the means to ensure their success. The ability of Iraqi auditing firms to employ e-auditing in auditing tasks is negatively affected by several technical, human, and organisational challenges. Furthermore, the researcher concluded that the e-Auditing process is consistent with the requirements of the auditing profession and what is emphasised by international standards and the financial framework applicable in this field.The researchers reached a set of recommendations, the most important of which is the need for Iraqi audit firms to adopt e-governance techniques, specifically e-auditing programs. It is also important to begin developing a comprehensive strategy that identifies the challenges they face to ensure their ability to adopt e-auditing in carrying out their audit tasks.